Investigation of two-phase flow instabilities under advanced PWR conditions. (June 2015) - Hwang, Dae-Hyun; Kwon, Hyouk; Kim, Seong-Jin
Highlights: Experimentally investigate density wave oscillation under advanced PWR condition. Establish and validate a linear stability analysis model in the frequency domain. Investigate CHF and stability margins under various operating conditions in SMART core. Abstract: The characteristics of two-phase flow instability under advanced pressurized water reactor (PWR) conditions are explored in this study. Density wave oscillations in vertical parallel tubes are experimentally investigated by employing three different test sections to observe the parametric effects of the axial power shape, unheated riser, and channel inlet throttling on the onset of flow instability (OFI). A critical heat flux (CHF) accompanied by flow oscillation is indicated under certain test conditions with high pressure and/or low inlet subcoolings. A frequency-domain linear stability analysis code, called ALFS_F, was developed on the basis of one-dimensional two-phase mixture equations and a reactivity feedback model with point neutron kinetics and lumped parameter heat conduction equations. The mass flux at OFI conditions and the oscillation periods are calculated by the ALFS_F to compare with the experimental data. The thermal margin characteristics are illustrated with a comparative analysis of OFI and CHF margins under the core conditions of SMART, which is an integral-type advanced PWR being developed at KAERI.